The influence of physical fitness on pressure pain threshold of elderly women. Issue 3 (July 2017) - Alfieri, Fábio Marcon; Lima, Alessandra Rodrigues de Souto; Oliveira, Natália Cristina de; Portes, Leslie Andrews
Summary: Several factors may influence pressure pain threshold (PPT), including physical fitness. However, only a few authors have studied this relationship. The aim of this study was to investigate the relationships between muscle strength, functional capacity (ability to perform physical work and activities of daily living) and PPT in elderly women. This observational cross-sectional study involved 75 healthy women aged between 60 and 75 years. Volunteers underwent an evaluation consisting of anthropometry, functional capacity, muscle strength and PPT assessment by algometry in the following muscles: biceps brachii, flexor carpi ulnaris, flexor carpi radialis, vastus medialis, vastus lateralis and gluteus maximus. Mean age of the 75 volunteers was 66.8 ± 4.6 years old. No significant correlations were found between handgrip or elbow flexion strength and PPT in the upper limb muscles evaluated. The same was observed regarding functional capacity, lower limbs strength and PPT in lower limb muscles. Functional capacity and muscle strength did not correlate with PPT in healthy elderly women.